Supported Decision-Making and Paradigm Shifts: Word Play or Real Change? - Stavert, Jill (Frontiers in Psychiatry, 2021)
Article 12(3) CRPD requires states parties to provide access by persons with disabilities to the support they may require in exercising their legal capacity. This is to ensure that the rights, will and preferences of persons with disabilities are enjoyed on an equal basis with others (Articles 12(1)(2) and (4) CRPD). Moreover, the Committee on the Rights of Persons with Disabilities has made it clear that supported decision-making must replace substitute decision-making arrangements as these are discriminatory and deny equal enjoyment of the right to exercise of legal capacity for persons. At the same time, there is ongoing debate as to whether or not the absence of substitute decision-making regimes is essential for the non-discriminatory realization of an individual’s rights, will and preferences to be achieved. To resolve this debate, however, specific attention needs to be paid to the CRPD message on what it actually means to give effect to the equal and non-discriminatory enjoyment of rights for all. In the context of persons with mental disabilities this requires looking beyond human rights simply in terms of limiting unwarranted interventions to the proactive removal of obstacles to full rights enjoyment and the creation of environments that respect and support such enjoyment. With this in mind this paper will therefore critically consider the use of supported decision-making within existing substitute decision-making regimes with particular reference to Scotland’s mental health and capacity laws. It will consider the challenges this poses and whether it is indeed possible to adapt existing regimes to achieve CRPD compliance. In doing so, it is suggested that a full appreciation of the overarching CRPD message about equality and non-discrimination in the enjoyment of rights is required to bring about such compliance.